Ressentis sur les Mooc dans une université - Thierry Gobert (Centre National d'Enseignement à Distance, 2015)
In 2013, the French Ministry of Higher Education and Research launched the "France université numérique" project (FUN). The purpose of that MOOC portal is to position innovative technology at the educational process. Universities, even those already involved in the project, reacted to that announcement. The present paper explores the sometimes strong reactions of academics and researchers, including those involved in the new project. Based on an action-research methodology, it aims at identifying their perceptions and even at getting these to evolve, and at bearing on practices. The method includes three steps: collecting a corpus of the initial representations academics had (1), introducing FUN, enhancing interest in it and explicating the university's major digital projects (2), presenting two MOOC, and reflecting on the potential integration of similar educational models (3). The results show the importance of the perceptions of the concerned parties in an innovative undertaking, and the role research action can play to sustain it.